Effect of zirconia surface treatments on the shear bond strength of veneering ceramic - Inas H Kareem; Haitham J Al-Azzawi (College of Dentistry/ University of Baghdad, 2014)
Background: The aim of the study was to investigate the effect of surface treatments of zirconia (grinding and sandblast with 50μm, 100 μm) on shear bond strength between zirconia core and veneering ceramic. Material and methods: Twenty-eight presintered Y-TZP ceramic specimens (IPS e.max ZirCAD, Ivoclar vivadent) were fabricated and sintered according to manufacturer's instructions. The core specimens were divided randomly in to 4 groups, group 1: no surface treatment, group2: zirconia specimens were ground with silicon carbide paper up to1200 grit under water cooling, group3: zirconia specimens were ground and sandblast with 100 μm alumina, group 4: zirconia specimens were ground and sandblast with 50 μm alumina. Surface roughness of specimens were analyzed by surface profilometer, then veneering ceramic (IPS e.max ceramic, Ivoclar vivadent) was applied on the specimens& fired according to manufacturer's instructions. All specimens were subjected to shear force in a universal testing machine at a crosshead speed of 1mm/min. The shear bond strength values were analyzed with one-way ANOVA; the fractured surfaces were examined with a stereo-microscope to observe the failure mode. Results: The mean of shear bond strength values in MPa were 24.75 for group 4, (17.72) for group 3, (17.68) for group2, (14.61) for group 1.The airborne-particle abrasion with 50μm group showed significantly higher bond strength than other groups. The airborne-particle-abraded with 100 μm group was not significantly different from grinding group. Conclusion: With limit of this study, the sandblast with 50 μm alumina was enhance the SBS between zirconia &veneering ceramic, and zirconia-veneering ceramic bonding is not only influenced by surface roughness. But also may be other factors.